Strategi Penghimpunan Dana Zakat, Infaq dan Sedekah di Masa Pandemi Covid 19 (Studi Komparatif pada Dhu’afa Tersenyum dan Lazismu Kalimantan Selatan) - Mahyuni - -; Selvia Humaira (P3M Politeknik Negeri Banjarmasin, 2021)
The Amil Zakat Institution (LAZ) requires a good strategy in collecting Zakat, Infaq, and Alms (ZIS) funds so that optimal Zakat, Infaq and Alms funds can be collected. The Covid-19 pandemic, which requires to reduce face-to-face activities to prevent the transmission of the Covid-19 virus, requires the Amil Zakat Institution to determine the right strategy so that the Covid-19 pandemic situation does not affect the decline in the collection of Zakat, Infaq and Alms funds. This study aims to find out and compare strategies for collecting zakat, infaq, and alms funds during the Covid-19 pandemic at 2 (two) Amil Zakat Institutions (LAZ), namely Dhu'afa Tersenyum and LAZISMU South Kalimantan. This research method is a qualitative method. Data collection techniques used interviews, documentation studies, and literature studies. The data obtained were then processed and then the data were analyzed descriptively and comparatively. The results showed that the two LAZs had some similarities in the socialization media used, payment methods, muzakki characteristics, and zakat consultation methods which were carried out both online and offline. Meanwhile, the difference can be seen from the use of officers where at LAZISMU South Kalimantan still deploys officers directly to carry out socialization to the community. Keywords: Dhu'afa Tersenyum, LAZISMU South Kalimantan, ZIS Fundraising Strategy